2004
DOI: 10.1080/09629350400008844
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nitric oxide synthase and transforming growth factor‐beta in crush‐injured tendon and synovium

Abstract: This study examined the expression of inducible nitric oxide synthase (iNOS) and transforming growth factor-beta (TGF-beta) in macrophage infiltrates within crush-injured digital flexor tendon and synovium of control rats and rats treated with N(G)-nitro-1-arginine methyl ester (L-NAME) (5 mg/kg). Release of TGF-beta from organ cultures of tendon, muscle, and synovium, and the effects of L-NAME treatment (in vitro and in vivo), on adhesion of peritoneal macrophages to epitenon monolayers were also investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…MMP-2 was demonstrated to be involved in this process (575). In addition, it was also suggested that NO may regulate satellite cell migration (104) and prevent fibrosis by inhibiting transforming growth factor-␤ signaling during muscle regeneration (126).…”
Section: Systemic Milieumentioning
confidence: 99%
“…MMP-2 was demonstrated to be involved in this process (575). In addition, it was also suggested that NO may regulate satellite cell migration (104) and prevent fibrosis by inhibiting transforming growth factor-␤ signaling during muscle regeneration (126).…”
Section: Systemic Milieumentioning
confidence: 99%
“…In contrast, most studies have focused mainly on the role of TGF-␤s in adult tendon and ligament pathology and wound healing. Thus, elevated protein and mRNA levels of TGF-␤ have been demonstrated in pathological Achilles tendons and during healing of injured tendons and ligaments (Natsu-ume et al, 1997;Fenwick et al, 2001;Darmani et al, 2004;Tsubone et al, 2004;Dahlgren et al, 2005). Exogenous application of TGF-␤1 and -␤2 significantly increased expression of collagen types I and III, and improved the mechanical properties of healing tendons or ligaments (Spindler et al, 2003;Kashiwagi et al, 2004;Anaguchi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…TGF-beta has been reported to induce the inhibition of NO production by macrophages through decreasing the stability and translation of mRNA in the NOS and increasing its degradation (Gilbert and Herschman, 1993;Owens et al, 1996;Darmani et al, 2004). Bauer et al (1999) reported diminished NO production following administration of TGF-beta 1 using a noninflammatory wound repair model (Bauer et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TGF-beta induced the inhibition of nitric oxide production by macrophages through decreasing the stability and translation of mRNA for the NOS (Gilbert and Herschman, 1993;Darmani et al, 2004). However, there has been limited research into alterations such as those in lipid peroxidation and antioxidant status in oral mucosa which heals more quickly than skin wounds.…”
Section: Introductionmentioning
confidence: 99%